Implementation of PJOK Learning Media at the Elementary School Level During the COVID-19 Pandemic in Padang Jaya District North Bengkulu - Feby Elra Perdima; Suwarni; Dwi Anggara (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine the application of learning media and the implementation of PJOK learning during the Covid-19 period in Padang Jaya District, North Bengkulu. This type of research is qualitative. The subjects of this study involved 7 PJOK teachers, and 35 elementary school students. Instruments and data collection techniques using observation, questionnaires and interviews. The data analysis technique uses data reduction, data presentation, drawing/conclusion and verification. Based on the results of research on PJOK learning media during the Covid-19 pandemic that used learning media with whatsapp/online and did not get a percentage of 50% of the medium criteria. Based on the results of research from PJOK teachers, 62.32% good criteria and 69, 21% good criteria for students. The results obtained through observation.